Pendidikan Multikultural Yang Berlandaskan Pada Buah-Buah Roh (Galatia 5:22-23) Demi Kerekatan Dan Keutuhan Bangsa Indonesia - Lanny I.D Koroh (Matheteuo: Religious Studies, 2022)
This article discusses Multicultural Education Based on the Fruits of the Spirit (Galatians 5:22-23) for the sake of the Unity and Integrity of the Indonesian Nation. The diversity of ethnic groups (ethnics) in Indonesia, which number in the hundreds, is recognized and realized as the pillars of a diverse Indonesia. Indonesian-ness is not only imagined but Indonesian-ness that exists. That is why the right to life of every ethnic group with its rich culture, customs, traditions, language, and even its future, must be guaranteed. Every ethnic group has long had a living space, history, tradition, myth, and legend to strengthen its identity. The living space of ethnic groups, large or small several citizens still has the same right to live, position, and national and state roles in this country. Marginalization can occur. Moreover, subtle and systemic destruction violates human rights—equal rights and status for all religions, including belief in God Almighty as a tribal religion. Everyone should be given the same space and opportunity to live and an equal position. Thus, the domination of the majority and the tyranny of the minority should not be given the opportunity state to develop. There is an "original habitat" for each tribe with its cultural heritage, customs, traditions, language, and literature that must be preserved and maintained.